Penerapan Model PjBL melalui Proyek Giving Directions untuk Meningkatkan Keterampilan Berbicara Bahasa Inggris-Indonesia Siswa Kelas V SD Kristen Kasih Bangsa Serui Papua - Anni Maria; Selviana Vindi Mamori (Civiliza Publishing, Indonesia., 2026)
This study was conducted to improve the English–Indonesian speaking skills of fifth-grade students at SD Kristen Kasih Bangsa Serui, Papua, through the implementation of the PjBL model using a Giving Directions project. A qualitative Classroom Action Research design based on the Kemmis and McTaggart model was employed, involving two cycles of planning, action, observation, and reflection. Twenty-eight students participated in the study. Data were collected through classroom observations, speaking performance tests, and documentation, while speaking ability was evaluated using pronunciation, vocabulary, grammar, fluency, and comprehension criteria. The findings demonstrated a consistent improvement in students' speaking performance, with the mean score increasing from 59.8 in the pre-cycle to 73.8 in Cycle I and 88.0 in Cycle II. Learning mastery also improved from 0% to 46.4% and finally reached 100%. It was concluded that PjBL effectively enhanced speaking competence by providing authentic and collaborative learning experiences. The findings offer practical guidance for integrating project-based activities into elementary English instruction, although the study was limited to one class and one learning topic.